Effectiveness of FVD-BIS for protecting a base-isolated high-rise building against resonance - Karimi, Mohammad Reza Bagerzadeh; Genes, Mehmet Cemal (Techno-Press, 2021)
Seismic isolation is a remedy for providing earthquake resistant features for structural components, nonstructural components, and contents of building systems. However, its performance may become counterproductive under the effect of near-field ground motions, which may cause an increased structural response due to resonance. In this paper, the responses of a high-rise building and a low-rise building, which are isolated with lead core rubber bearing (LCRB) subjected to near-field pulse period ground motions, are investigated. The results indicate that the selected isolation system and base-isolated buildings are period-dependent, making them vulnerable to near-field pulse-period ground motions as a result of resonance. For this investigation, several ground motions are generated synthetically with a specific pulse period, which is set close to the fundamental period of the subjected base-isolated high-rise building to facilitate resonance. To mitigate the responses of the subjected base-isolated buildings and since the fundamental natural period of a structure is not affected by fluid viscous dampers (FVD), FVD was implemented with LCRB forming a fluid viscous damper-base isolation system (FVD-BIS). Note that some investigations have suggested that FVD can improve the performance of base-isolated buildings, but the impact of FVD-BIS on base-isolated high-rise and low-rise buildings at the time of resonance remains ambiguous. This study has illustrated that the intensity of the resonance phenomenon can be sharply mitigated in a base-isolated high-rise building using FVD-BIS.
Keywords: Fluid Viscous-Base Isolation System (FVD-BIS); Fluid Viscous Damper (FVD); Lead Core Rubber Bearing (LCRB); pulse-like ground motions; resonance phenomenon